Belize : Selected Issues Paper. (IMF Staff Country Reports; Country Report ;, 2018)
This Selected Issues paper analyzes Belize's correspondent banking relationships (CBR). All affected banks have found some replacements CBRs and alternative ways of processing cross border transactions. The analysis uses a dataset based on a bank-level survey and the IMF staff's minimum scope framework. Pressures from the loss of correspondent banking relationships appeared to be easing. The US dollar continued to dominate CBR transactions, but its share has been declining. CBR pressures appear to be easing but risks remain. Risks include CBR counterparty credit risk and withdrawal risk, in addition to remaining supervisory gaps which could potentially add to CBR pressures. The importance of CBR in supporting economic activity and financial stability is highlighted in several studies. The results of the study results are consistent with the view that the recovery in CBRs in Belize will support credit growth and economic activity. Ensuring the availability and timely access to beneficial ownership of legal persons and arrangements established in Belize would limit the opportunity for their misuse and improve the transparency and the reputation of the sector.